Evaluating Post-Insertion Complications and Patient Satisfaction of Conventional Complete Dentures: A Retrospective Study - Lavanya Ajay Sharma; Navodika Yaparathna; Nithya Cheruka; Peng Shao; Menaka Abuzar (MDPI AG, 2024)
Conventional complete dentures remain to be an important treatment for edentulous patients, especially those of low socioeconomic status. This study is a retrospective analysis that aims to elucidate influencing factors of post-insertion complications and patient satisfaction. Clinical records of 164 patients who received both maxillary and mandibular complete dentures at an Australian university teaching clinic were assessed and analysed. The parameters considered include reason for attendance, presenting clinical status, experience of operator, numbers of appointments for fabrication and adjustment, post-insertion complications and events, and patient satisfaction. The differences among selected attributes were analysed using a Mann-Whitney test, Chi-square test, or Kruskal-Wallis test where applicable, while the relationships between discrete variables were assessed by Kendall's correlation. First, the number of appointments for fabrication differed significantly between female (6.8 ± 1.8) and male patients (6.2 ± 1.3; p = 0.025) and between student (6.7 ± 1.7) and professional operators (6.0 ± 1.1; p = 0.015). The number of appointments for adjustment was significantly associated with patient age (τb = 0.167, p = 0.003) and sharply declined after the first three months. Second, post-insertion pain was the most frequent complication, and it was significantly more associated with the mandible than the maxilla (χ2 = 21.670, p = 0.000). Similarly, mandibular complete dentures were also significantly more associated with post-insertion reline than the maxillary (χ2 = 8.804, p = 0.003). Lastly, patient satisfaction was significantly associated with patient attendance with old/worn dentures (χ2 = 9.468, p = 0.002), as well as the absence of retention/stability issues (χ2 = 41.712, p = 0.000), post-insertion reline (χ2 = 29.300, p = 0.000), or denture replacement (χ2 = 13.968, p = 0.000). Dissatisfied patients had a significantly higher age (70.9 ± 11.0 vs. 66.2 ± 12.6; p = 0.023) and number of appointments for adjustment (4.9 ± 3.5 vs. 3.1 ± 2.1; p = 0.001) than satisfied patients. In summary, these findings revealed the above factors that influence the fabrication process, post-insertion complication, and patient satisfaction of conventional complete dentures. Future research may include analysis of cases completed at private practices and consideration of other potentially relevant factors such as denture usage and mental status.